Enhancing Nursing Students’ Speaking Skill in Presenting Healthcare Education by Using TikTok Application - Kaban, Susiana (IJLECR (International Journal of Language Education and Cultural Review), 2023)
Speaking skills are the skills that give us the ability to communicate effectively. They involve using appropriate vocabulary, voice, and nonverbal cues to convey messages in a passionate, thoughtful, and convincing manner. Healthcare education need a good speaking skill; an ability to have a speech in a simple presentation in order to educating people about health. Teachers always need to look for an innovative and interesting media in teaching English speaking skill. TikTok application can be used as an interesting and effective learning medium which meets the learning needs of students who are millennials and actually attached to the digital world. This study was class room action research. The participant of this study were 40 students of Ners Undergraduates Program of STIKes Flora Academic Year 2022/2023 who were taking the English II course in the sixth semester. The research instruments were observation, interview, pre-test, and post-test. The steps of using TikTok in learning speaking for presenting healtcare education: (a) the teacher made 2 TikTok videos; an explanation video and healtcare education video as an example, (b)teacher explained using TikToks video and then nursing students watch the videos and got the knowledge; (c)students practice pronunciation using TikTok videos, (d) the teacher asked the students to create their own video using TikTok application and posted it. The improvement score from posttest cycles I to posttest cycle II was about 8.32. The nursing students enjoyed learning speaking English with this application.